Effects of brand alliance on brand equity. Issue 1 (3rd September 2018) - Ma, Baolong; Cheng, Feiyan; Bu, Jingjing; Jiang, Jiefan
Abstract : Purpose: Although brand alliance has become quite ubiquitous in the marketplace and attracted considerable interest amongst researchers, little research has investigated its effects on the brand equity of partners. The purpose of this paper is to demonstrate why and how brand alliance affects the brand equity of the partners in an alliance. Design/methodology/approach: The hypotheses were tested by analysing the data of 260 participants in China, which were collected from an experiment. Findings: This research draws five conclusions: the brand equity of a pre-alliance partner has a positive effect on brand alliance evaluation; product fit and brand fit amongst partners also have a positive effect on brand alliance evaluation; alliance brand evaluation has a positive impact on the brand equity of a post-alliance brand; the brand equity of a pre-alliance partner exerts a positive effect on the brand equity of a post-alliance partner; and the spillover effect of brand alliance for a weak brand is stronger than that of a strong brand in an asymmetrical brand alliance. Originality/value: This research introduces brand equity into the field of brand alliance. From the perspective of consumer perception, the authors measure brand equity and provide insights for a company to effectively enhance brand equity through brand alliance. The authors explore ways to increase the brand equity of partners through brand alliance. Additionally, the authors discuss the spillover effects of the brand equity of partners in symmetric and asymmetric brand alliances.